"Green" Podlasie Opera and Philharmonic in the City of Białystok: Context - Idea - Architecture. Issue 8 (February 2019) - Tokajuk, Andrzej
Abstract: Podlasie Opera and Philharmonic in Bialystok was created as part of the project called European Centre for the Arts. It was located in the place of the degraded amphitheatre and became one of the most interesting public building realized in Poland in the beginning of the 21st century. The new building of the Podlasie Opera was being constructed during 2005 - 2012. The general designer of the whole complex was studio of Marek Budzynski Architect. The author of this article has taken the trial of using a kind of parametrical methodology analysing urban composition, architectural concept and sustainable aspects of the new Podlasie Opera House. A context of the location of the new building is very important - the religious hill and the small Orthodox Church of St. Maria Magdalena's, ancient cemeteries: Orthodox and Jewish, contemporary Central Park - the city centre of Bialystok. The first project contained of the building of the opera, the multiscreen cinema and an underground parking. The project was based on 3 ideas – the idea of Hope and Co-existing, the idea of the axis of the Podlasie Art. And the idea of the Tradition. In the Project of the new Opera we can see many ecological aspects: omnipresent greenery - plants on elevations, poles, roofs, introduced on a few different levels. The New Podlasie Opera and Philharmonic is the example of new tendency in the architecture of 21st century. We can call it New Romanticism or Modernist Romanticism. Other critics situate the style of the new building between the classical postmodernism and the individualistic postmodernism. But for sure we can see here the connection of culture and nature using the architectural art. Also the synthesis of opposites, synthesis of the tradition with the modernity, integration of architecture and the landscape.